ANALISIS KUALITAS PRODUK DAN LAYANAN YANG MEMPENGARUHI KEPUASAN PELANGGAN (STUDI KASUS HYPERMART MALL SKA PEKANBARU) - Vina Octavia; Fajar Restuhadi; Eliza Eliza (Indonesian Journal of Agricultural Economics, 2018)
This study was conducted to determine the factors that affect customer satisfaction in shoppingat Mall SKA Pekanbaru City. This research was conducted at SKA Mall Pekanbaru. Themethod used is survey method with non probability sampling of accidental sampling. Thenumber of samples taken is 200 samples. The analysis used in this research is StructuralEquation Modelling (SEM) method. The results showed that reliability and responsiveness arethe factors that mostly influence consumer satisfaction of all factors. The result showed thatreliability has value of Critical Ration (CR) of 3,756 with p = *** and responsiveness has CRvalue of 1,972 with p <0.05 = 0,046.